2022
DOI: 10.3389/fcvm.2022.899739
|View full text |Cite
|
Sign up to set email alerts
|

New R2-CHA2DS2-VASc score predicts no-reflow phenomenon and long-term prognosis in patients with ST-segment elevation myocardial infarction after primary percutaneous coronary intervention

Abstract: AimsEvaluating the prognostic validity of new R2-CHA2DS2-VASc score for no-reflow phenomena and long-term prognosis in patients following primary percutaneous coronary intervention (PCI) with ST-elevation myocardial infarction (STEMI).Materials and methodsFrom January 2017 to December 2018, a total of 401 patients with STEMI were continuously enrolled. According to the cut-off value, the patients were separated into two groups: R2-CHA2DS2-VASc < 3 group (n = 275) and R2-CHA2DS2-VASc ≥ 3 group (n = 126).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, smoking appears to favor intramyocardial hemorrhage [254,256]. A higher CHA2DS2-VASc Score is also associated with the increased risk of CNR after primary PCI [257,258]. Pre-infarction angina appears to reduce the incidence of CNR, potentially due to salutary effects of ischemic preconditioning [259,260].…”
Section: Individual Susceptibility To Cnrmentioning
confidence: 99%
“…However, smoking appears to favor intramyocardial hemorrhage [254,256]. A higher CHA2DS2-VASc Score is also associated with the increased risk of CNR after primary PCI [257,258]. Pre-infarction angina appears to reduce the incidence of CNR, potentially due to salutary effects of ischemic preconditioning [259,260].…”
Section: Individual Susceptibility To Cnrmentioning
confidence: 99%
“…The prognosis of STEMI varies among patients and is largely dependent on risk factors ( 6 ). Previous studies have demonstrated that multiple risk factors and their interactions are associated with the long-term prognosis of patients with STEMI treated with primary PCI ( 7 , 8 ). Patients with STEMI who are stratified into subgroups according to these risk factors have distinct clinical profiles, resulting in different MACEs risks ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%